(untitled) (Anwer Khan Modern Medical College Journal, 2023)
The efficacy and duration of protective immunity made by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is unknown. In studies of immunity to other corona viruses, loss of immunity can occur within 1–3 years. But how long this SARS-CoV-2 gives immunity to reinfection is not well understood. In this case report, we describe a 40-year-old male patient presented with two different episodes of SARS-CoV-2 infection (COVID-19 illnesses) within two months period. AKMMC J 2021; 12(1) : 66-68